Sephardism Spanish Jewish history and the modern literary imagination - Halevi-Wise, Yael, 1965- (Stanford, Calif. : Stanford University Press, 2012)
"In this book, Sephardism is defined not as an expression of Sephardic identity but as a politicized literary metaphor"--Provided by publisher.
Introduction: through the prism of Sepharad: modern nationalism, literary history, and the impact of the Sephardic experience / Yael Halevi-Wise -- The myth of Sephardic supremacy in nineteenth-century Germany / Ismar Schorsch -- Writing Spanish history in nineteenth-century Britain: the Inquisition and "the secret race" / Michael Ragussis -- "Rachel, ou l'Auto-da-fé": representations of Jews and the Inquisition in the French grand opera La juive (1835) / Diana R. Hallman -- The strange career of the Abarbanels from Heine to the Holocaust / Jonathan Skolnik -- Sephardim and neo-Sephardim in Latin American literature / Edna Aizenberg -- The life and times of the picaro-converso from Spain to Latin America / Yael Halevi-Wise -- Facing Sepharad, facing Israel and Spain: Yehuda Burla and Antonio Gala's Janus profiles of national reconstitution / Stacy N. Beckwith -- Sephardic identity and its discontents: the novels of A.B. Yehoshua / Bernard Horn -- "Le juif espagnol": the idea of Sepharad among colonial and postcolonial Francophone Jewish writers / Judith Roumani -- Sephardism in Latina literature / Dalia Kandiyoti -- Sir Salman Rushdie sails for India and rediscovers Spain: postmodern constructions of Sepharad / Efraim Sicher -- Postscript: Rebecca Goldstein's Spinoza / Yael Halevi-Wise.
Description based on print version record.
Keywords: Sephardim in literature; Jews, Spanish, in literature; Literature, Modern -- History and criticism; BIOGRAPHY & AUTOBIOGRAPHY / Literary; Electronic books